Orgo-Seq integrates single-cell and bulk transcriptomic data to identify cell type specific-driver genes associated with autism spectrum disorder - Elaine T. Lim; Yingleong Chan; Pepper Dawes; Xiaoge Guo; Serkan Erdin; Derek J. C. Tai; Songlei Liu; Julia M. Reichert; Mannix J. Burns; Ying Kai Chan; Jessica J. Chiang; Katharina Meyer; et al. (Nature Communications, 2022)
Cerebral organoids can be used to gain insights into neuropsychiatric disorders. Here the authors carry out RNAseq characterization from organoids derived from donors with autism spectrum disorder to identify associated cell type specific driver genes.